Valoración de los beneficios del parto vertical versus el parto por cesárea en mujeres de 20-30 años atendidas en el Hospital Sagrado Corazón de Jesús, Quevedo, Los Ríos, octubre 2018- abril 2019 - Contreras Solorzano, Guillermo Javier (2019)
Worldwide, in recent years is promoting humanized delivery, given the high rate of deliveries by cesarean section is a surgical procedure that involves risks for both the mother and the newborn, while humanized delivery also known childbirth vertical is a procedure that facilitates the birth process and is much more favorable for the mother and the newborn. This research describes the benefits of vertical delivery and cesarean delivery in women who have been treated at the Sacred Heart of Jesus Hospital. This work was carried out with 78 pregnant women. The study methods used were qualitative, descriptive and cross-sectional, comparative, the technique that was used was the survey, the information was collected through the application of a questionnaire. The results obtained were that 89% of the participating women have no knowledge of vertical delivery and only 11% if they know about this delivery procedure, in relation to the caesarean section rate it was established that 86% of pregnant women have given birth by this procedure and 14% did it for vertical delivery, a situation that is worrisome because of the risks posed by the cesarean section procedure and that contrasts with the advantages and benefits of vertical delivery. In this context arises the urgent need to promote the initiative of health organizations committed to promoting vertical delivery given the advantages offered to both mother and child